Empirical Evidence for Intraspecific Multiple Realization? - Strappini, Francesca; Martelli, Marialuisa; Cozzo, Cesare; di Pace, Enrico (Frontiers in Psychology, 2020)
Despite the remarkable advances in behavioral and brain sciences over the last decades, the mind/body (brain) problem is still an open debate and one of the most intriguing questions for both cognitive neuroscience and philosophy of mind. Traditional approaches have conceived this problem in terms of a contrast between physicalist monism and Cartesian dualism. However, since the late sixties, the landscape of philosophical views on the problem has become more varied and complex. The Multiple Realization Thesis (MRT) claims that mental properties can be (or are) realized, and mental processes can be (or are) implemented by neural correlates of different kinds. Thus, MRT challenges the psychoneural type-identity theory and the corresponding reductionism. Many philosophers have acknowledged the a priori plausibility of MRT. However, the existence of empirical evidence in favor of intraspecific, human multiple realizations of mental processes and properties is still controversial. Here we illustrate some cases that provide empirical evidence in support of MRT. Recently, it has been proposed that foveal agnosic vision, like peripheral vision, can be restored by increasing object parts’ spacing (Strappini et al., 2017a; Crutch and Warrington, 2007). Agnosic fovea and normal periphery are both limited by crowding, that impairs object recognition, and provides the signature of visual integration. Here we define a psychological property of restored object identification and we cross-reference the data of visually-impaired patients with different etiologies. In particular, we compare the data of two stroke patients, two patients with posterior cortical atrophy (PCA), six cases of strabismic amblyopia, and one case with restored sight. We also compare these patients with unimpaired subjects tested in the periphery. We show that integration (i.e. restored recognition) seems to describe quite accurately the visual performance in all these cases. While the patients have different etiologies and different neural correlates, the unimpaired subjects have no neural damage. Thus similarity in the psychological property given the differences in the neural substrate can be interpreted in relation to MRT and provide evidence in its support. Finally, we will frame our contribution within the current debate concerning MRT providing new and compelling empirical evidence.